The genetic basis of plumage polymorphism in the black sparrowhawk - Rodseth, Edmund (Department of Molecular and Cell Biology, 2023)
This study aimed to examine the molecular basis of several aspects of plumage colouration in the black sparrowhawk (Accipiter melanoleucus), an African diurnal bird of prey. The adults of this species occur in two discrete morphs, light and dark. Light morph individuals were found to differ from dark morph individuals in the concentration of eumelanin in contour feathers from the breast feather tract, with light morph breast feathers containing no detectable eumelanin, while dark morph breast feathers contained similar amounts of eumelanin to the uniformly dark-coloured back feathers. No polymorphisms associated with morph were found in the coding regions of the melanogenesis genes melanocortin 1 receptor (MC1R), agouti signalling protein (ASIP), or proopiomelanocortin (POMC). However, the expression levels of several genes involved in melanogenesis differed between the two morphs, with light morph developing breast feathers showing significantly higher levels of expression of ASIP and lower expression of downstream melanogenesis genes tyrosinase (TYR), tyrosinase-related protein 1 (TYRP1), and microphthalmia-associated transcription factor (MITF) than the dark morph. The black sparrowhawk also shows distinct rufous juvenile plumage, which is a particularly common trait in raptors. The genetic basis of juvenile plumage was investigated, and eumelanin and pheomelanin levels were found to be tightly correlated in the breast and back contour feathers of juvenile black sparrowhawks. The amount of both eumelanin and pheomelanin produced was negatively correlated with expression of ASIP, as was expression of downstream melanogenesis genes TYR, MITF, and TYRP1, the same genes that appear to determine adult plumage morph. Pheomelanin levels were found to correlate with fault bar formation, and thus may reflect acute or chronic stress experienced during feather development, but not with condition or parental plumage morph. Finally, possible pleiotropic effects of morph were investigated. Dark morphs were found to have a lower haemoparasite infection intensity than light morphs, confirming previously published results, but differences in telomere length were not associated with parasite infection or morph in this species. However, sex was found to be significantly associated with telomere length, with males having longer telomeres than females.